A prospective randomized study to compare weekly versus tri-weekly cisplatin-based concurrent chemoradiation in the treatment of locally advanced carcinoma cervix - Arshad Mollah,; Shyam Sharma,; Koustav Biswas,; Linkon Biswas,; Srikrishna Mandal, (Asian Journal of Medical Sciences, 2022)
Background: Concurrent chemoradiotherapy with cisplatin is the standard treatment for locally advanced carcinoma cervix. Cisplatin can be given either as weekly or a tri-weekly regimen with radiotherapy. However, there were few studies comparing both, so our study aimed at comparing weekly versus tri-weekly cisplatin-based chemoradiation in terms of loco-regional control and acute toxicity profile. Aims and Objectives: To compare the treatment response and acute toxicity profile of thse two concurrent chemotherapy schedule. Materials and Methods: Patients with non-metastatic, squamous cell carcinoma of uterine cervix International Federation of Gynecology and Obstetrics stage IB2-IVA were randomized into two arms-control arm patients received external beam radiotherapy (50Gy in 25 fractions over 5 weeks) with concurrent weekly cisplatin (40mg/m2), and study arm patients received radiotherapy with same dose, along with tri-weekly concurrent cisplatin (75 mg/m2) for two cycles. After that, all patients received brachytherapy 21 Gee/3 fractions, one fraction/week. All patients were followed up weekly during treatment and then monthly for at least a period of 6 months for evaluation of toxicity and treatment response. Results: Six weeks after treatment completion, complete treatment response was comparable in both the arms(43.33% vs. 46.67%, P=0.35). Incidences of leucopenia were significantly high in weekly cisplatin arm (P=0.002).Nephrotoxicity of higher grade was also numerically more in control arm (P=0.654). However, treatment compliance was better in tri-weekly cisplatin arm, reflected by reduced treatment interruptions (46.67% vs. 53%). Conclusion: Tri-weekly cisplatin-based concurrent chemoradiation is equally effective as weekly cisplatin-based approach with comparable acute toxicity in treatment of carcinoma cervix.